2013
DOI: 10.1016/j.ecolind.2012.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Extending the viability theory framework of resilience to uncertain dynamics, and application to lake eutrophication

Abstract: )>IJH=?J Resilience, the capacity for a system to recover from a perturbation so as to keep its properties and functions, is of growing concern to a wide range of environmental systems. The challenge is often to render this concept operational without betraying it, nor diluting its content. The focus here is on building on the viability theory framework of resilience to extend it to discrete-time stochastic dynamical systems. The viability framework describes properties of the system as a subset of its state s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 29 publications
(65 reference statements)
0
48
0
1
Order By: Relevance
“…These additional uncertainties are mostly related to formalization of the nexus between social, economic, and environmental sub-systems interacting with the system-of-interest (the system assessed). Although methods such as Exploratory Modeling Analysis [18,157] and reliability theory [158], and viability theory [159] might be helpful to address uncertainties, the major source of uncertainties are the assumptions made when mathematically defining dynamic relationships among system parameters (especially in further parts of the system). Overcoming this challenge requires further attention from the scientific community and in-depth research about how things affect each other.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…These additional uncertainties are mostly related to formalization of the nexus between social, economic, and environmental sub-systems interacting with the system-of-interest (the system assessed). Although methods such as Exploratory Modeling Analysis [18,157] and reliability theory [158], and viability theory [159] might be helpful to address uncertainties, the major source of uncertainties are the assumptions made when mathematically defining dynamic relationships among system parameters (especially in further parts of the system). Overcoming this challenge requires further attention from the scientific community and in-depth research about how things affect each other.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…In this study, we measure robustness as the probability of a control to keep the system in a viable state. This operational definition is close to the one used by Rougé et al (2013).…”
Section: Adaptability and Robustness In Rangelandsmentioning
confidence: 79%
“…Viability theory makes it possible to define resilience without reverting to the concept of a steady state (Martin, 2004;Martin et al, 2011), and to define robustness against state uncertainty (Alvarez and Martin, 2011;Rougé et al 2013). In our study, we further developed this approach and showed how viability could be used to define robustness against dynamic stochasticity and management adaptability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations